Sulfated proteoglycans as modulators of neuronal migration and axonal decussation in the developing midbrain - Cavalcante,L.A. (2003)
Proteoglycans are abundant in the developing brain and there is much circumstantial evidence for their roles in directional neuronal movements such as cell body migration and axonal growth. We have developed an in vitro model of astrocyte cultures of the lateral and medial sectors of the embryonic mouse midbrain, that differ in their ability to support neuritic growth of young midbrain neurons, and we have searched for the role of interactive proteins and proteoglycans in this model. Neurite production in co-cultures reveals that, irrespective of the previous location of neurons in the midbrain, medial astrocytes exert an inhibitory or nonpermissive effect on neuritic growth that is correlated to a higher content of both heparan and chondroitin sulfates (HS and CS). Treatment of astrocytes with chondroitinase ABC revealed a growth-promoting effect of CS on lateral glia but treatment with exogenous CS-4 indicated a U-shaped dose-response curve for CS. In contrast, the growth-inhibitory action of medial astrocytes was reversed by exogenous CS-4. Treatment of astrocytes with heparitinase indicated that the growth-inhibitory action of medial astrocytes may depend heavily on HS by an as yet unknown mechanism. The results are discussed in terms of available knowledge on the binding of HS proteoglycans to interactive proteins, with emphasis on the importance of unraveling the physiological functions of glial glycoconjugates for a better understanding of neuron-glial interactions.